A COLUMN-LEVEL ACCESS CONTROL MECHANISM FOR DATABASE OUTSOURCING SERVICE - Hue, Pham T. B.; Thuy, Dong T. B.; Thuc, Nguyen D. (Vietnam Journal of Science and Technology, 2012)
ABSTRACT Database outsourcing is emerging today as a successful paradigm allowing data owners toship their data to the external service provider for the distribution of resources. An importantproblem to be addressed in this paradigm concerns the protection of outsourced data fromunauthorized access even from the service provider’s server, which is not fully trusted. Severalencryption schemes and access control mechanisms have been suggested to protect theoutsourced data from unauthorized disclosure. However, by implementing these approaches,data owners are not capable of controlling and protecting the disclosure of the individualsensitive attributes of their data. Therefore, we propose a new column-level access controlmechanism that is based on subkeys, which would allow a data owner to further control theaccess to his data at the column-level. We also propose a new mechanism to efficiently reduce the number of keys maintained by a data owner in cases when the users have different access privileges to different columns of the data being shared. Keywords: Access control, column-level access control, database encryption.